Relationship Between Spiritual Health and Life Satisfaction in Iranian Elderly People: The Mediating Role of Forgiveness - Asmar Shahbazi Chahartaq; Majid Yousefi Afrashteh; Zekrollah Morovati (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Older people adults may feel incompetent due to impaired mental and physical function. It is very important to improve their satisfaction with life by increasing their spiritual health. The present study aims to determine the relationship between spiritual health and life satisfaction of the elderly in Iran and assess the mediating role of forgiveness. Methods & Materials This is a correlational study with a cross-sectional design using path analysis. The study population included older people in Zanjan, Iran, in 2022, of whom 301 were selected using a convenience sampling method. They completed the satisfaction with life scale, spiritual well-being scale, and forgiveness scale. SPSS software version 26 and LISREL software, version 10.2 were used to analyze data using path analysis. Results The mean age of the elderly was 68.84 years. According to the results of the research, spiritual health has a relationship directly and indirectly with the satisfaction of the lives of the elderly. The mediating role of passing was also confirmed. The results show the good fit of the study model. The results showed a direct and significant relationship between spiritual health and life satisfaction (β=0.23 and P<0.001) and between forgiveness and life satisfaction (β=0.39 and P<0.001). Conclusion Iranian older adults' satisfaction with life can be improved by improving their spiritual health and the ability to forgive. The findings of this study can be used in planning to improve life satisfaction of older adults in Iran.